Transnationalisation et stratégies d’investissement - Minian, Isaac (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1985)
The rapid development of transnational firms and banks during the 1960's and 1970's, and their search for increasing autonomy vis-à-vis the national governments of host countries is the main theme of this paper. The author concludes that MNE and MNB are increasingly able to avoid national regulations. However the massive use of the U.S. dollar in international transactions gives the American government a disproportionate influence on global economic relations and trends. MNE try to maximize short term return on investments and the international coherence and integration of their own network. All these trends contribute to the desarticulation of the national economies of the host countries. Besides, MNE conceive strategies for "socializing" (i.e. transferring to the host state) many costs and risks. The whole picture is one of diminishing state capabilities in the host countries.